2009
DOI: 10.1016/j.jmb.2009.04.041
|View full text |Cite
|
Sign up to set email alerts
|

Active-Site Gating Regulates Substrate Selectivity in a Chymotrypsin-Like Serine Protease

Abstract: We report here the first structure of a member of the IgA protease family at 1.75Å resolution. This protease is a founding member of the Type V (autotransporter) secretion system and is considered a virulence determinant among the bacteria expressing the enzyme. The structure of the enzyme fits that of a classical autotransporter in which several unique domains necessary for protein function are appended to a central, 100 Å long β-helical domain. The N-terminal domain of the IgA protease is found to possess a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
71
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(75 citation statements)
references
References 77 publications
4
71
0
Order By: Relevance
“…Despite their abundance and the increasing amount of data linking AT proteins to bacterial virulence, very little structural information is available at a molecular level for these proteins. In fact, AT proteins are significantly underrepresented in the Protein Data Bank (PDB), with only 1 fulllength AT structure, 7 AT passenger domains, 5 AT β-domains, and 12 small domains of trimeric autotransporters deposited among the ∼87,500 structures currently available in the PDB (9,18,(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36). None of these entries belong to the large family of AIDA-I-type AT proteins from Gamma-Proteobacteria (3,16).…”
Section: Discussionmentioning
confidence: 99%
“…Despite their abundance and the increasing amount of data linking AT proteins to bacterial virulence, very little structural information is available at a molecular level for these proteins. In fact, AT proteins are significantly underrepresented in the Protein Data Bank (PDB), with only 1 fulllength AT structure, 7 AT passenger domains, 5 AT β-domains, and 12 small domains of trimeric autotransporters deposited among the ∼87,500 structures currently available in the PDB (9,18,(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36). None of these entries belong to the large family of AIDA-I-type AT proteins from Gamma-Proteobacteria (3,16).…”
Section: Discussionmentioning
confidence: 99%
“…The side chain points inward in the ␤-helical lumen and stacks with other aromatic residues farther up in the stem. Sequence alignments of SPATEs and related serine protease ATs showed that a Trp residue is most often found at this position, although, for example, the Haemophilus influenzae ATs IgA protease (14) and Hap (46) have a Tyr and Phe at this position, respectively. ␤-Helix structures are usually capped both at the C terminus and the N terminus to prevent inappropriate interactions with the hydrophobic core and the unpaired strands (16).…”
Section: Discussionmentioning
confidence: 99%
“…Structural analysis of the secreted AT passengers pertactin (11), VacA (12), hemoglobin protease (Hbp) (13), and IgA protease (14) reveals a common overall topology: a long stem or stalk consisting of a right-handed ␤-helix to which other functional domains are appended. A ␤-helix is an extremely stable fold of ␤-strands, in this case of triangular rungs comprising three strands, that are interrupted by loops with variable length and are stacked to form a cross ␤-structure (15,16).…”
mentioning
confidence: 99%
“…Then, in a coordinated fashion, the carboxy-terminal ␤-barrel is inserted into the outer membrane, and the passenger domain is translocated to the bacterial surface, although the mechanism by which these processes occur is poorly understood. At the bacterial surface, the passenger domains of all autotransporters for which the structures have been solved adopt a long, righthanded parallel ␤-helical conformation (20,22,37,52).…”
Section: Discussionmentioning
confidence: 99%